A time-space window between Eocene karst bauxite genesis and the first molasse deposition in the Dinaric Foreland Basin in the North Dalmatia, Croatia - Brčić, Vlatko; Dunkl, István; Mindszenty, Andrea; Brlek, Mihovil; Trinajstić, Nina; Bajo, Petra; Bauluz, Blanca; Mišur, Ivan; Karius, Volker; Šuica, Sanja; Kukoč, Duje; Yuste, Alfonso; et al. (Frontiers in Earth Science, 2023)
Karst bauxite deposits in the North Dalmatian Piggyback Basin (NDPGB) are a part of the Mediterranean bauxite belt, which is the largest European bauxite deposit zone; however, there is a general lack of information regarding the genesis, age, and precursor of the bauxite deposits in this region. In this study, we combined detrital zircon U-Pb geochronology with compositional, mineralogical, and morphological data from four bauxite locations in the NDPGB to provide a new palaeogeographical and palaeoenvironmental evolution model for the Lutetian to Rupelian timeframe of the NDPGB. The Eocene climatic conditions began with the Paleocene-Eocene Thermal Maximum event (PETM, ∼56 Ma), followed by the Early Eocene Climatic Optimum (EECO, ∼49 Ma) and Middle Eocene Climatic Optimum (MECO, ∼40 Ma), and were completed as a cooling trend culminating around the Eocene/Oligocene boundary ( 34 Ma), with a shift towards an icehouse climate. These events were coeval with the continuous drift of the African continent towards Eurasia and the subsequent closure of the western part of the former Neo-Tethys Ocean associated with massive volcanic activity. Based on the bauxite deposits of the NDPGB, Early Eocene limestones formed in the last phase of the long-lasting Adriatic Carbonate Platform. The Middle Eocene orogenic activity resulted in an elevation in this area. High average temperatures, accelerated hydrological cycles and precipitation, and intensive continental weathering with increased volcanic carbon input resulted in favourable conditions for the development of karst bauxites. Further Upper Eocene tectonic deformation of the NDPGB area resulted in the development of bauxite traps and enabled redeposition of the initial bauxite material. Subsequently, the bauxite deposits were covered with clastic carbonate molasse derived from the intensive erosion of the young Dinaric orogeny. The implications of this study are as follows. First, it provides new information on the timing of bauxitization in the area by providing the first radiometric zircon geochronology, which refined and restricted the time window for bauxite formation in this region. Additionally, our results provide new perspective on the possibility of aeolian precursors in karst bauxite formation and provide new constraints on the first tectonic marks of the initial Dinaric orogeny.